Between Anzac Day and Waitangi Day - Czerwińska Anna (Studia Anglica Posnaniensia, 2017)
This paper discusses the historical background and significance of the two most important national holidays in New Zealand: Waitangi Day and Anzac Day. Waitangi Day is celebrated on the 6th February and it commemorates the signing of the Treaty of Waitangi between British representatives and a number of Māori chiefs in 1840. Following the signing of the treaty New Zealand became effectively a British colony. Anzac Day is celebrated on 25th April, i.e., on the anniversary of the landing of soldiers of the Australian and New Zealand Army Corps (ANZAC) on the Gallipoli peninsula in Turkey in 1915, during World War One. There are three major differences between these two holidays: the process of those days becoming national holidays, the level of contestation, and the changing messages they have carried. The present study analyzes the national discourse around Anzac Day and Waitangi Day in New Zealand, and attempts to reveal how the official New Zealand government rhetoric about national unity becomes deconstructed. The following analysis is based on a selection of online articles from the New Zealand Herald and Stuff published in Auckland and Wellington, respectively. Both cities are populated by multi-ethnic groups, with Auckland featuring the largest Māori population.